A Man’s Search for Meaning in Sex: Management of Compulsive Sexual Behaviour Disorder - Srishti Sharma; Abhinav Agrawal; Himani Mittal (Journal of Psychosexual Health)
The term compulsive sexual behaviour disorder (CSBD) involves a person’s excessive and recurring obsession with sexual fantasies, impulses and behaviours that are unpleasant for them and/or cause psychosocial harm. Due to the paucity of research on the topic, no specific guidelines are available for the treatment of CSBD, however, preliminary studies suggest a few options. This case report aims to discuss the management of a clinical case of CSBD that presented the increased number of sexual encounters with commercial sex workers leading to high-risk behaviours. After a detailed history and, physical and mental state examination, a diagnosis was established and management was done with a combination of pharmacotherapy and psychotherapy. A progressive improvement was noted over six months. The case report highlights the need for timely diagnosis and effective treatment, which can improve distress, dysfunction and overall quality of life.